Functional neuroimaging and the bilingual brain - PERANI, DANIELA (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2003)
The advent of non-invasive neuroimaging techniques opened up a new era in the investigation of language organization in healthy individuals. Positron emission tomography (PET) and functional magnetic resonance imaging (fMRI) enabled neuroscientists to examine the mechanisms of cognitive functioning and to probe on-line the close relationship between brain and mind. This is an overview of the most relevant results that have so far been achieved in the field of the cerebral basis of bilingualism by using functional neuroimaging techniques. I will discuss which conclusions may be drawn from these studies considering, in particular, the potential role of a number of variables which have been suggested to play a role in the shaping of language representations in the bilingual brain. Consistent results indicate that second language (L2) proficiency and language exposure and the age of L2 acquisition are very important determinants of the cerebral representation of languages in bilinguals/polyglots. Neuroimaging technologies, such as positron emission tomography (PET) and functional magnetic resonance imaging (fMRI) allow to capture “in vivo” images of the physiology of mind processes. For instance, they show how specific regions of the brain “light up” when subjects are engaged in linguistic activities, such as listening to stories or producing words. Hence, they provide us with a powerful tool for mapping the language faculty in the human brain. The issue of language and brain mechanism becomes more intriguing if we consider the unique capacity of the human brain to acquire, store, and use more than one language. Actually, more than half of the world population speaks more than one language. It becomes clear that related questions deserve serious attention, whether they are theoretical or practical in nature. How do bilingual people understand and produce language? How do people learn and acquire a second language? How does the human brain represent and organize multiple languages? Are there different or overlapping brain areas responsible for the language processes of different languages? And in the case of differential cerebral organization of languages, is this due to the age of second language (L2) acquisition or rather to the degree of L2 proficiency? These are just a few of the many questions that can be raised in this respect. The latter three issues are of particular interest to neuroscientists and may be well addressed with the advances of functional neuroimaging techniques.